2021
DOI: 10.1186/s12888-021-03466-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a digital mental health intervention for individuals with psychosis - a multi-country qualitative study

Abstract: Background Implementation of psychosocial interventions in mental health services has the potential to improve the treatment of psychosis spectrum disorders (PSD) in low- and middle-income countries (LMICs) where care is predominantly focused on pharmacotherapy. The first step is to understand the views of key stakeholders. We conducted a multi-language qualitative study to explore the contextual barriers and facilitators to implementation of a cost-effective, digital psychosocial intervention,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Other identified facilitators, such as DIALOG+ providing better insight into patients’ conditions, facilitating clinical work and improving therapeutic relationships, were also previously described in literature. 14 All these identified benefits of implementing DIALOG+, combined with the frequently mentioned feasibility of the intervention, represent favourable features in terms of achieving sustainability of DIALOG+. It is encouraging to see that clinicians perceived certain benefits of this intervention in patients, such as increased proactivity and improvement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other identified facilitators, such as DIALOG+ providing better insight into patients’ conditions, facilitating clinical work and improving therapeutic relationships, were also previously described in literature. 14 All these identified benefits of implementing DIALOG+, combined with the frequently mentioned feasibility of the intervention, represent favourable features in terms of achieving sustainability of DIALOG+. It is encouraging to see that clinicians perceived certain benefits of this intervention in patients, such as increased proactivity and improvement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This finding emerged across all participant groups and was in accordance with the existing literature on intervention sustainability in LMICs. 14 Furthermore, financial resources were often mentioned during discussion about other barriers, indicating that this barrier might be crucial in facilitating successful sustainability of DIALOG+.…”
Section: Discussionmentioning
confidence: 99%
“…Few patients reported the need for training due to their lack of familiarity with smartphones/tablets, and the poor mental health of patients can be a barrier (Pemovska et al, 2021 ). An Indian study reported that the challenges faced during tele-rehabilitation were: network issues and only one device at home for multiple users.…”
Section: Discussionmentioning
confidence: 99%
“…This app-based intervention, delivered via a tablet, computer, or smartphone is a psychosocial intervention, to enable the therapeutic effectiveness of usual meetings between patients and clinicians. Earlier RCTs, using DIALOG+, in both high and low-income countries, have demonstrated improvement in quality of life and reduction in symptoms ( 32 , 33 ). In the current situational analysis, the use of a device to deliver new psychosocial interventions was noted to be both a barrier and a facilitator.…”
Section: Novel Interventionsmentioning
confidence: 99%